Executive Functions Influence on Memory Process in Patients with Paranoid Schizophrenia and Bipolar Disorders with and without Psychotic Symptoms. A Pilot Study. (4th August 2021) - García-Laredo, Eduardo; Castellanos, Miguel Ángel; Badaya, Esperanza; Paúl, Nuria; Yubero, Raquel; Maestú, Fernando; Molina, Juan D.; Chacón, José
Abstract: The objective of the present study was to evaluate whether declarative memory deficits are related to executive function deficits (EF), since they could be a consequence of a poor organization of the material to memorize. This interaction between both cognitive processes can be studied simultaneously in a single task such as the Test of Memory Strategies (TSM). 23 patients with paranoid schizophrenic disorder, 11 with bipolar disorder with psychotic symptoms, 13 with bipolar disorder without psychotic symptoms and 15 healthy subjects were evaluated with the TSM; with the memory test Texts A and B (subtest of the Barcelona neuropsychological assessment battery), which assesses short-term and immediate recall without the influence of EF; and with the Trail Making Test (TMT): Part A (sustained attention) and Part B (executive control). The patients groups and the control group showed an improvement in memory performance across each of the TSM conditions. However, this facilitating effect of the strategies differed among the groups (the patients with higher EF deficits showed less improvement). Regarding these results, we conclude that this cognitive process cannot be independent of EF. However, due to the pilot nature of this study, it would be recommended to replicate these findings in new studies.